Engineering-Driven Approach for the Structural Design of Geometrically Complex Modular Artificial Reefs - Fábio Cruz; Isabel B. Valente; Dmytro Maslov; Tiago Miranda; Eduardo B. Pereira (Applied Sciences)
Over the years, artificial reefs with diverse forms and functions have become increasingly important in maritime engineering and ecosystem restoration plans, with socio-economic and ecological impacts on marine ecosystems. However, due to the increasing complexity of designs and durability requirements, the current structural design approaches lack adequate documentation and standardization. This work addresses this challenge by detailing an engineering-driven approach for the structural design of artificial reef structures made of reinforced concrete or composite steel and concrete. This study establishes the premises for the structural design, followed by the quantification of actions based on standards and recommendations for marine structures. Hydrodynamic and numerical models were utilized to assess the effects of these actions on the structure. A cross-section organic design was then implemented, followed by a parametric study exploring various structural and material combinations for optimization. This study validates the developed design methodology combining hydrodynamic actions and strength analysis for complex modular artificial reef structures of 3 to 15 m size, specifically tailored for open waters. The results confirm the applicability and reliability of the developed design methodology, demonstrating its potential for guiding future numerical and experimental studies on modular artificial reef structures in open waters.